THU0651-HPR ONLINE EDUCATION YIELDS SIGNIFICANT GAINS IN RHEUMATOLOGISTS' KNOWLEDGE OF THE ROLE OF ENTHESITIS IN THE DIAGNOSIS AND MANAGEMENT OF PSA. (2nd June 2020) - Stan, A.; Calle, M.; Schoonheim, P.; Mease, P. J.
Abstract : Background: Physicians face challenges staying up-to-date with the latest research and accessing the ever-growing field of knowledge is time-consuming. Online education can make these clinician's tasks more efficient and less time-consuming. Objectives: As part of a larger curriculum, we developed an online CME activity titled: "Enthesitis in Psoriatic Arthritis: Disease, Diagnosis and Decisions". The goal of this study was to assess whether this online CME accredited video discussion improves physicians' understanding of the role of enthesitis in the diagnosis and management of patients with psoriatic arthritis (PsA) in clinical practice. Methods: Rheumatologists participated in an online CME activity (https://www.medscape.org/viewarticle/910671 ) consisting of a 30-minute video discussion between 2 experts with accompanying slides. Educational effect was assessed using a 4-question repeated pairs, pre-/post-assessment. A chi-square test was used to determine if a statistically significant improvement ( P <.05 significance level) existed in the number of correct responses from the pretest and posttest scores. Cramer's V was used to estimate the level of impact of the education. The CME activity launched on March 28, 2019, and the data were collected through June 7, 2019. Results: A total of 145 rheumatologists completed the pre- and post activity assessments. Overall the activity had a signficiant impact ( P <.0001) on rheumatologists' knowledge of the role of enthesitis in the diagnosis and management of PsA, with a Cramer's V value of 0.153 indicating a noticeble educational impact. The average percentage of correct responses rose from 54% pre-activity to 69% post-activity. A repeated pairs analysis showed that 22% of rheumatologists improved their knowledge and 47% reinforced their knowledge, respectively. The change in percentage of correct responses from pre- to post-assessment for all questions are shown in table. Almost 40% of rheumatologists had a measurable improvement in confidence in their ability to evaluate the presence of enthesitis according to a clinical exam or ultrasound. Conclusion: This online CME activity significantly improved rheumatologists' understanding of role of enthesitis in the diagnosis and management of PsA. However, there is clearly room for further improving physicians' knowledge of clinical trial outcomes with biologics in patients with enthesitis, since 44% of rheumatologists provided incorrect answers to question 3 post-education. This topic can be addressed in future education. Acknowledgments: This CME-certified activity was supported by independent funding from Novartis AG. Disclosure of Interests: Adriana Stan Grant/research support from: The CME-certified activity was supported by an independent educational grant from Sandoz., Marinella Calle Grant/research support from: This CME-certified activity was supported by an independent educational grant from Novartis AG, Peter Schoonheim Grant/research support from: This CME-certified activity was supported by independent funding from Sandoz., Philip J Mease Grant/research support from: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – grant/research support, Consultant of: Abbott, Amgen, Biogen Idec, BMS, Celgene Corporation, Eli Lilly, Novartis, Pfizer, Sun Pharmaceutical, UCB – consultant, Speakers bureau: Abbott, Amgen, Biogen Idec, BMS, Eli Lilly, Genentech, Janssen, Pfizer, UCB – speakers bureau